ПРОБЛЕМЫ НАЦИОНАЛЬНОГО САМОСОЗНАНИЯ В ТВОРЧЕСТВЕ АЛИ БЕКА ГУСЕЙНЗАДЕ - Фарзалиева, У. Ф. (Journal of Oriental Studies, 2016)
Автор мақаласында Али Бек Гусейнзаде шығар- машылығындағы ұлттық өзін-өзі тану мәселесіне тоқталады. In the article are analysed the ideas of A. Guseynzada about national self-consciousness, his attitude to the ancient Chinese chroniclers and their erroneous ideas about Turkic peoples. It is emphasized that awakening of national selfconsciousness struck chauvinistic policy of tsar Russia a blow.